2020
DOI: 10.1111/are.14989
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dietary methionine requirement for juvenile sea cucumber Apostichopus japonicus selenka

Abstract: This trial was conducted to determine the optimal dietary methionine requirement for juvenile sea cucumber Apostichopus japonicus selenka. Six isonitrogenous and isoenergetic experimental diets were formulated with graded methionine levels (0.18%, 0.37%, 0.57%, 0.78%, 0.96%, 1.10% dry matter). Each diet was assigned randomly to triplicate groups with 30 sea cucumbers juveniles with initial body weight 12.14 g in a recirculated aquaculture system for 56 days. Survival rate was not affected by dietary methionine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The predicted dietary phosphorus level is 0.63% for maximum growth. Aquaculture Nutrition compared to the growth data from other studies [17,[48][49][50]. These positive growth responses fit quadratic regression models and thus confirm that phosphorus deficiency or excess could hinder the growth of A. japonicus as reported in a previous study on tiger shrimp [26].…”
Section: Intestinal Oxidation Resistancesupporting
confidence: 79%
See 3 more Smart Citations
“…The predicted dietary phosphorus level is 0.63% for maximum growth. Aquaculture Nutrition compared to the growth data from other studies [17,[48][49][50]. These positive growth responses fit quadratic regression models and thus confirm that phosphorus deficiency or excess could hinder the growth of A. japonicus as reported in a previous study on tiger shrimp [26].…”
Section: Intestinal Oxidation Resistancesupporting
confidence: 79%
“…During the feeding trial, A. japonicus grew from 9.99 g to 14.67–21.60 g with an acceptable SGR (0.71–1.11%/d), as compared to the growth data from other studies [ 17 , 48 50 ]. These positive growth responses fit quadratic regression models and thus confirm that phosphorus deficiency or excess could hinder the growth of A. japonicus as reported in a previous study on tiger shrimp [ 26 ].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Studies have reported that vitamin B 6 can enhance the secretion of digestive enzymes by promoting the growth and development of digestive organs, thereby improving the digestion and absorption capacity [37]. It has been reported that adding vitamin B6 into the diet of Apostichopus japonicus can improve the expression of intestinal amylase [38]. A study by Wei showed that vitamin B 6 can improve the ability of Rhodeus sinensis Gunther to resist hypoxia [39].…”
Section: Discussionmentioning
confidence: 99%